2021
DOI: 10.3390/ijerph18094471
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Enhance Knowledge and Practical Skills of Triage amongst Nurses Working in the Emergency Departments of Rural Hospitals in South Africa

Abstract: Purpose: Lack of knowledge and practical skills on triage remains a global problem, especially within rural hospitals, and very little is known about enhancing the knowledge and skills of emergency nursing staff in rural hospitals of South Africa. The objective was to describe the perceived strategies for enhancing knowledge and practices of triage among nurses working in the emergency departments (EDs) of rural hospitals in South Africa. Research methods: A descriptive qualitative research design was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
4
0
2
Order By: Relevance
“…that more than two-thirds of participants were between the ages of 20 and 30 (21) . Concerning gender, it was clear that the majority of nurses were females, this result was matched with Phukubye et al (2021) who stated that more than half of the studied nurses were females (22) . It was also found that two thirds of nurses were married.…”
Section: Figure (3): Correlation Between Total Nurses' Knowledge and ...supporting
confidence: 84%
“…that more than two-thirds of participants were between the ages of 20 and 30 (21) . Concerning gender, it was clear that the majority of nurses were females, this result was matched with Phukubye et al (2021) who stated that more than half of the studied nurses were females (22) . It was also found that two thirds of nurses were married.…”
Section: Figure (3): Correlation Between Total Nurses' Knowledge and ...supporting
confidence: 84%
“…Despite the importance of the role of standard triage and the triage nurses’ professional capability in saving lives, no study has directly evaluated this concept; however, the results of the studies that assessed the professional knowledge and clinical skills of the nurses showed a moderate level of clinical skills [ 11 ]. Studies conducted in the world and Iran suggest that there are serious concerns in these areas so that lack of professional knowledge and clinical skills in triage nurses has received attention as a global problem [ 14 ]. According to a study in Addis Ababa, Ethiopia in 2018, more than half of the participants had moderate levels of triage skill and its subdomains [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Triase juga meningkatkan alur pelayanan pasien di UGD dimana petugas triase akan memprediksi jenis jumlah sumber daya di UGD yang diperlukan guna mencapai keputusan akhir yang tepat yaitu pulang, rawat inap atau dipindahkan keluar dari UGD. Pengetahuan dan keterampilan diantara perawat gawatdarurat merupakan faktor penting untuk keperawatan yang berkualitas dalam perawatan di UGD (Phukubye et al, 2021).…”
Section: Pembahasanunclassified
“…Bagi petugas triase, pola pikir kritis ini sangat didukung oleh faktor intuisi atau insting. Hal tersebut dapat diperolah dengan bekal pengetahuan/ wawasan, pelatihan dan pengalaman (Phukubye et al, 2021).…”
Section: Pembahasanunclassified